Conservation of Amazonian aquatic mammals. Issue 5 (4th April 2021) - Brum, Sannie; Rosas‐Ribeiro, Patrícia; Amaral, Rodrigo de Souza; de Souza, Diogo Alexandre; Castello, Leandro; da Silva, Vera Maria Ferreira
Abstract: Aquatic mammals worldwide are highly threatened in freshwater ecosystems where they are affected by direct human activities (e.g. hunting) as well as indirect human alteration of freshwater ecosystems (e.g. dams, mining activity). Although aquatic mammals of the Amazon Basin are experiencing many growing threats, little is known about the escalating impacts on them, current limitations in protection mechanisms, and possible strategies to ensure their conservation. This study synthesizes the available information on Amazonian aquatic mammals, including the ecological characteristics of these species, key threats, population status and conservation prospects. Amazonian aquatic mammals comprise seven species – Inia geoffrensis, Inia boliviensis, Inia araguaiaensis, Sotalia fluviatilis, Trichechus inunguis, Pteronura brasiliensis and Lontra longicaudis – which are characterized by low reproductive rates and keystone ecosystem roles. These species are endangered mainly by biological resource use, natural ecosystem modifications, energy production and mining, and climate change. Although information is sparse, there is evidence that these threats are inducing population declines of Inia spp., and hindering the recovery of populations of P. brasiliensis . Protection mechanisms for these species mostly include national and international laws and agreements, legislation governing environmental licensing and protected areas. Each of these protection mechanisms, however, has limited capacity to protect Amazonian aquatic mammals, largely because they are poorly enforced, lack transnational coordination or require population trend data that do not exist. Reversing the current state of affairs for Amazonian aquatic mammals requires an integrated research and policy approach that, at a minimum, substantially increases the present capacity to monitor their population responses to human impacts, establishes effective enforcement of existing legislation and prevents further impacts from hydropower development. To implement such an approach, information on the ecology of these species is necessary to create public and scientific awareness.